Structural properties of tungsten-doped cobalt molybdate and its application in electrochemical oxygen evolution reaction - Doldet Tantraviwat (2018)
© 2018, Springer Science+Business Media, LLC, part of Springer Nature. New tungsten-doped CoMoO4(W-CoMoO4) was successfully synthesized by a simple co-precipitation method and investigated for a possible application in oxygen evolution reaction (OER). The effect of W6+doping on structure, morphology, and chemical compositions was investigated by X-ray diffraction spectroscopy, scanning electron microscopy, Fourier transform spectroscopy, Brunauer–Emmet–Teller surface area measurement, and X-ray photoelectron spectroscopy. Linear sweep voltammetry indicates that doping CoMoO4with an optimum W6+amount of 21 wt% provides higher current density at lower overpotential than other catalysts. Compared to undoped CoMoO4, the 21 wt% W-CoMoO4also shows a remarkable activity and excellent long-term stability in alkaline media. This superior activity is ascribed to the synergistic effect of increased oxygen vacancy, enhanced surface area, and possibly improved electrical conductivity upon W6+doping. The significances of this work are that the potential OER application of Co–W–Mo tertiary oxide, which has never been studied before, and the effect of non-3d high-valency metal (W) doping on OER activity enhancement are now being recognized.